Estrategias educativas para la enseñanza aprendizaje personalizado en la educación inicial 2 “A” de la Unidad Educativa Isabel La Católica - Bravo Mastian, Vilma (2023)
This research is carried out in order to be able to adequately evaluate which are the appropriate educational strategies for the teaching-learning process in the students of initial education 2 “A”, of the Isabel “La Católica” Educational Unit, therefore , objectives have been proposed that contribute to the analysis of this problem, based on analyzing educational strategies which are tools that facilitate teachers to give individual attention to each student, taking into account the skills and abilities that each one has, this is was given through the use of descriptive and analytical methodology that contribute to the analysis of the bases of the problem, with which, an adequate evaluation has been carried out of the educational strategies that will be implemented within the initial education of the institution where it is carried out. carried out the research, it is thus that the results obtained in terms of the surveys and observation sheet that have been used to demonstrate the prolonged development that the education and capacity of the initial education students has had, generating that they become better involved in the educational field and the relationship with his classmates, with the teacher and with the entire environment that surrounds him. Therefore, learning through educational strategies has contributed to school development, which has resulted in the use of more strategies that facilitate the teaching-learning process of each child.